Imagery and observational learning use and their relationship to sport confidence - Hall, C. R.; Munroe-Chandler, K. J.; Cumming, J.; Law, B.; Ramsey, R.; Murphy, L. (Journal of Sports Sciences, 2009)
The present study investigated 345 athletes' (male = 152, female = 193) use of observational learning and imagery for practice and at competition and how this related to sport confidence. The Functions of Observational Learning Questionnaire (Cumming et al., 2005), the Sport Imagery Questionnaire (Hall et al., 1998), and the Trait Sport Confidence Inventory (Vealey, 1986) were contextualized by asking participants to rate each item twice, once for practice and once for competition. The athletes reported using each of the different functions of observational learning and imagery in these situations, but the pattern of use differed. Whereas nearly all of the imagery functions were more frequently used at competition, the majority of observational learning functions were used more for practice. Cognitive specific and motivational general-mastery imagery were significant predictors of sport confidence in practice and competition, whereas the skill function of observational learning significantly predicted practice confidence only.